A pilot design of a protocol for a university-wide community-based occupational health screening project: HUMS2U - Pang, Nicholas Tze Ping; Sofeinah Didora Judip; Jeanny John; Erwani Minin; Noor Rajrinnie Rajak; Luqman Ridha Anwar; Helen Benedict Lasimbang; Mohd Nazri Mohd Daud; Sahipudin Saupin (Malaysian Journal of Medicine and Health Sciences, 2020)
University-wide healthcare programme are difficult to implement without complete protocols. This paper describes a collaborative academia-nursing programme to design a quick, user-friendly primary care screening toolkit, to be used at community level at each faculty in UMS. Methods: A Primary Care Condition Assessment Questionnaire was designed by family medicine physicians, mental health doctors, and public health physicians. The questionnaire was pilot tested in 2 different faculties. The Primary Care Condition Assessment Questionnaire was manualized, and a one-day intervention training programme was administered. Subsequently 19 nurses and assistant medical officers were trained in the questionnaire administration and given concurrent communication skills and collaborative practice training to operate the questionnaire. Qualitative assessments of abilities to perform common primary health assessments were performed. Results: Trained nurses qualitatively felt they were more confident to perform primary care screening of common healthcare conditions and were able to deliver advice and refer screen-positive individuals to appropriate referral pathways. Conclusion: Public health programmes like HUMS2U put healthcare into the hands of nurses, allowing task-shifting to adequately trained non-specialist professions, and empowers nurses in basic non-communicable disease training and management. Further research will be performed to assess efficacy of the programme at all 23 faculties and departments of the university.